Social-cognitive factors influencing household decisions to grow orange-fleshed sweet potato in Uganda - Ndaula, S.; Sseguya, H.; Matsiko, F. (African Journals Online, 2020)
This study examined the role of social-cognitive factors in farmers’ decisions to cultivate orange-fleshed sweetpotato as a food-based approach to alleviating vitamin A deficiency among rural households in Uganda. Cross-sectional survey data collected from 341 randomly selected household level decision-makers drawn from two rural districts in Uganda were analysed using hierarchical regression. Perceived capability and perceived social approval significantly predicted household decisions to grow orange-fleshed sweet potato (p≤0.001). Overall, decision-makers’ subjective norms and control beliefs were found to be significant mediators (p≤0.01) of the orange-fleshed sweet potato acceptance process. These results point to a cardinal role for processes that create supportive social and cognitive environments in promoting the cultivation of bio-fortified technologies such as orange-fleshed sweet potato.